Reducing interfacial recombination for photovoltage enhancement in mesoscopic solar cells - Koh, Teck Ming (2015)
Mesoscopic solar cells, including dye-sensitized solar cells (DSCs), have been regarded as one of the promising low-cost energy conversion technologies for the next generation of solar cells. Inspired by natural photosynthesis, DSCs are built up from different components, handling light harvesting, charge transport and regeneration processes, in an appropriate energy level alignment. In traditional DSCs employing an I-/I3- electrolyte, the loss in potential, particular in overpotential for regeneration, has become the key drawback, which limits its power conversion efficiency. The newly emerging Co(II/III) redox couples have reduced the loss in overpotential, however, significant interfacial recombination between electrons in the conduction band of the semiconductor (usually TiO2) and electrolyte is a major concern in achieving an efficient device with a high photovoltage. This thesis focuses on reducing the interfacial recombination to achieve high photovoltages in liquid state DSCs through the modulation of electrolyte components, surface passivation and structural modification of cobalt-based redox mediators. In addition, the development of a new dopant for solid state perovskite solar cells is discussed. The first study involves the modulation of photovoltage by 4-tert-butylpyridine (TBP), an electrolyte additive, which greatly enhances the recombination resistance. Its viscous nature, however, leads to a mass transport limitation in the Co redox system, which lowers the cell’s photocurrent density, reconfirming the need for other additives in the Co(II/III) redox electrolyte. The second study involves the introduction of cyanobiphenyl derivatives as electrolyte additives in overcoming the mass transport limitation. An electrochemical impedance spectroscopy study revealed the interfacial recombination is greatly reduced, yielding higher photovoltage compared to the device with only TBP in electrolyte. The overall cell performance is enhanced with this additive and stable DSCs are achievable. The inadequate protection of the TiO2 surface by the electrolyte additive has led to the study on controlling the interfacial recombination by surface passivation. It has been ascertained that the use of alkanephosphonic acids assist in enhancing the recombination resistance and charge collection efficiency over a wide range of potentials. With the grafted TiO2 photoanode, the blocking of the interaction between TiO2 and electrolyte is significantly enhanced. The advantage of having bulky groups in disconnecting the contact between TiO2 and electrolyte was implemented in the new cobalt-based redox shuttle, MY14. The presence of isopropyl groups in MY14 reduces the back reaction without any mass transport limitations, as confirmed by the photocurrent transient measurements. Finally, in the solid state perovskite solar cell, the electrolyte was replaced by a solid state hole conductor (spiro-OMeTAD) which possesses more positive redox potential and results in higher photovoltage. The photovoltage is further improved through chemical doping of the hole conductor using the newly synthesized cobalt-based dopant, MY11. The conductivity of the hole conductor was increased by two orders of magnitude which guarantees better charge transport. MY11 exhibits deepest redox potential among all the current cobalt-based dopant and is important for doping a wide range of hole conducting materials for solution-processed photovoltaics.